2020
DOI: 10.48550/arxiv.2012.04671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Information Transfer with a Gravitating Bath

Hao Geng,
Andreas Karch,
Carlos Perez-Pardavila
et al.

Abstract: Late-time dominance of entanglement islands plays a critical role in addressing the information paradox for black holes in AdS coupled to an asymptotic non-gravitational bath. A natural question is how this observation can be extended to gravitational systems. To gain insight into this question, we explore how this story is modified within the context of Karch-Randall braneworlds when we allow the asymptotic bath to couple to dynamical gravity. We find that because of the inability to separate degrees of freed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
88
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(89 citation statements)
references
References 56 publications
1
88
0
Order By: Relevance
“…In the second part of the paper we used this dictionary to derive a formula for the mass of the graviton in the brane theory. The question whether graviton masses are important for the island formula has been discussed in [5,53,54]. One interesting observation to make is that apart from the near boundary limit, the formula for the graviton mass exhibits The solid line is computed numerically.…”
Section: Discussionmentioning
confidence: 99%
“…In the second part of the paper we used this dictionary to derive a formula for the mass of the graviton in the brane theory. The question whether graviton masses are important for the island formula has been discussed in [5,53,54]. One interesting observation to make is that apart from the near boundary limit, the formula for the graviton mass exhibits The solid line is computed numerically.…”
Section: Discussionmentioning
confidence: 99%
“…This picture naturally leads to a corresponding QES/island prescription in asymptotically flat space and demonstrates that the entropy in the semi-classical approximation SpRq is actually an average over an ensemble associated to a Hilbert space of baby universe states on the island. However, we also note that the applicability of the QES/island prescription when gravity is dynamical in the bath region, and indeed the Page curve itself, has been questioned in recent works, on general grounds[53,54] and within the framework of Karch-Randall braneworlds scenario[55,56]. We thank Suvrat Raju for correspondence on this and related issues.…”
mentioning
confidence: 86%
“…Second, replica wormhole saddle which is a wormhole connecting various copies of the original black hole. It was observed that the replica saddle leads to the contribution of the islands and enforces the entropy Furthermore, the island rule have been explored extensively for various black holes in flat and AdS spacetimes such as: JT gravity [9,[17][18][19][25][26][27][28], two-dimensional dilaton gravity [29][30][31][32][33] , in higher dimensions [33][34][35][36][37][38][39][40][41][42], higher derivative gravity theories [43], charged black holes [44][45][46][47], pure BTZ black hole microstates 3 [48][49][50], and black holes coupled to gravitating baths [50][51][52][53]. See also [4] for a very nice review on the topic.…”
Section: Introductionmentioning
confidence: 99%